Analyzing COVID-19 Discourse as Traumatic Speech Acts in Pakistan - Dr. Tamsila Naeem; Dr. Hassan Shakeel Shah; Dr. Faiqa Khaliq (Al-Qanṭara, 2022)
Abstract Judith Butler’s theory of performativity has significantly shaped socio-psychological viewpoints. This study uses mixed method approach to scrutinize the traumatic aspects of COVID-19 discourse, which create disturbing effects on psychological state of people in Pakistan. The theoretical framework applied in this study is based on the Judith Butler’s Theory of Excitable Speech, propounded by her in 1997. The data are collected through an online survey questionnaire, which consists of close-ended questions along with the comments of the respondents. The collected data are qualitatively and quantitatively analyzed. For quantitative data analysis, descriptive statistics calculator was used and for qualitative analysis, the possible conditions of traumatic speech acts are applied. The findings demonstrate that the COVID-19 discourse have appeared to be the most dangerous traumatic speech acts, which are liable to hit people at large in Pakistan. The study suggests that proper attention should be given to psychological health of people, which is being affected under multiple corona threats spread through its discourse. Keywords: COVID-19 discourse, traumatic speech act, excitable speech, psychological trauma, behavioural shifts